Patterns of earthquake-related mortality at a whole-country level: New Zealand, 1840–2017. Issue 1 (February 2020) - Abeling, Shannon; Horspool, Nick; Johnston, David; Dizhur, Dmytro; Wilson, Nick; Clement, Christine; Ingham, Jason
Fatalities directly or indirectly attributed to New Zealand earthquakes in the time period 1840–2017 inclusive were identified and classified by context and cause of death. There have been at least 489 deaths primarily attributed to 21 New Zealand earthquakes with Modified Mercalli Intensities (MMIs) of VII or greater, and an additional 11 deaths resulting from secondary earthquake causes (e.g. relief efforts). Earthquake-related deaths were caused by building damage (431 deaths, 88%), ground damage (34 deaths, 7%), or other causes (24 deaths, 5%). Damage to at least 95 unreinforced masonry (URM) buildings resulted in 272 deaths, and damage to five reinforced concrete (RC) buildings resulted in 145 deaths. Daytime earthquakes were more deadly than nighttime earthquakes, and mortality rates showed a significant increase with MMI. Mortality rates were nearly evenly distributed between males and females, the median age of death was 38 years, and the elderly population (>80 years) had the highest mortality rate.